Effects of leukocyte–platelet-rich fibrin (L-PRF) in different intraoral bone grafting procedures: a systematic review (2019)
This systematic review aimed to assess the effects of leukocyte–platelet-rich fibrin (L-PRF) on bone regeneration, soft tissue healing, and postoperativecomplications in patients undergoing ridge preservation, ridge augmentation, andmaxillary sinus augmentation procedures. A comprehensive literature search wasconducted by two independent reviewers. Only randomized and non-randomizedcontrolled clinical trials were selected. Outcome data were extracted and criticallyanalyzed. A total of 17 articles were included in the qualitative synthesis. The use ofL-PRF in extraction sockets was associated with a modest beneficial effect bydecreasing alveolar ridge remodeling and postoperative pain when compared tonatural healing. In contrast, the use of L-PRF in maxillary sinus augmentationprocedures was not associated with more favorable outcomes, and its use in ridgeaugmentation procedures could not be assessed adequately as it was reported in onlyone study. No meta-analysis could be conducted due to the heterogeneity of theselected studies. The limited evidence on the effects of L-PRF in intraoral bonegrafting procedures highlights the need for further research to fully assess its clinicalindications, with an emphasis on the application of standardized protocols for thepreparation of this autologous product.Key words: leukocytes; platelet-rich fibrin;maxillary sinus; alveolar ridge augmentation;sinus floor augmentation; tooth extraction;growth factors.Accepted for publication 7 June 2018Available online 7 July 2018Leukocyte–platelet-rich fibrin (L-PRF)was initially introduced by Dr JosephChoukroun in the early 2000s as a thera-peutic adjuvant to enhance wound healingand tissue regeneration following intraoralsurgical procedures1. L-PRF is considereda second-generation platelet concentrate,characterized by a simplified preparationmethod without any biochemical manipu-lation or exogenous additives to the bloodsample2. For its preparation, venous bloodis harvested and centrifuged in a tubeInt. J. Oral Maxillofac. Surg. 2019; 48: 250–262https://doi.org/10.1016/j.ijom.2018.06.003, available online at https://www.sciencedirect.com0901-5027/020250 + 013 ã 2018 International Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.